TROUBLESHOOTING PC VCCS BENGKULU PLANNER DI PERUM LPPNPI CABANG PALEMBANG BANDAR UDARA INTERNASIONAL SULTAN MAHMUD BADARUDDIN II: Nadira Armelya Kaban, Dian Anggraini, Febriaman Zega, Redhi Rizki Pratama - Kaban, Nadira Armelya; Dian Anggraini; Febriaman Zega; Redhi Rizki Pratama (Cipta Kind Publisher, 2024)
ABSTRACT: On The Job Training is teaching, research and practice at the Indonesian Aviation Polytechnic Curug which aims to improve teaching and improve the vision and scope of certain activities in the field, as well as improve the welfare of the community and students. OJT is mandatory for Cadets of the Indonesian Aviation Polytechnic Curug to improve the learning outcomes obtained from their training so far and increase opportunities to explore various learning outcomes. work This is reflected in the work environment and context, as well as the ability to produce the skills and knowledge expected of professionals, especially aviation engineers. Telecommunication tools for aviation that are easy and efficient to use in the aviation world and we often hear are Voice Communication Control Systems. VCCS coordinates the entire communication network used by ATC by switching radio and telephone voice channels automatically based on the radio frequency address or telephone number displayed on the touch screen panel, making it easier for Air Traffic Control to communicate, both radio and telephone, to ATC, technicians, and to pilots. VCCS consists of two main parts, namely server and client. The server is the processing center and the center for controlling input and output switching, while the client part is the device used by the user in operating VCCS. On The Job Training merupakan pengajaran, penelitian dan praktek di Politeknik Penerbangan Indonesia Curug yang bertujuan untuk meningkatkan pengajaran dan meningkatkan visi dan ruang lingkup kegiatan tertentu di lapangan, serta meningkatkan kesejahteraan masyarakat dan mahasiswa. OJT wajib dilakukan oleh Taruna Politeknik Penerbangan Indonesia Curug untuk meningkatkan capaian pembelajaran yang diperoleh dari pelatihannya selama ini dan memperbesar kesempatan untuk mengeksplorasi berbagai capaian pembelajaran. pekerjaan Hal ini tercermin dalam lingkungan dan konteks kerja, serta kemampuan menghasilkan keterampilan dan pengetahuan yang diharapkan dari para profesional, khususnya insinyur penerbangan. Alat Telekomunikasi untuk penerbangan yang mudah dan efisiensi digunakan di dunia penerbangan dan sering kita dengar adalah Voice Communication Control System. VCCS mengkoordinir seluruh jaringan komunikasi yang digunakan oleh ATC dengan men-switch saluran suara radio dan suara telepon secara otomatis berdasarkan alamat frequency radio ataupun nomor telepon yang ditampilkan pada touch screen panel sehingga memudahkan Air Traffic Control dalam melakukan komunikasi baik itu radio maupunn telepon ke ATC, teknisi, maupun ke pilot. VCCS terdiri dari dua bagian utama, yaitu server dan client. Server merupakan pusat processing dan pusat pengontrolan switching input dan output, sedangkan bagian client adalah perangkat yang digunakan oleh user dalam pengoperasian VCCS.